2015
DOI: 10.4269/ajtmh.14-0787
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Dissemination in Cutaneous Leishmaniasis Following Local Treatment

Abstract: Abstract. Cutaneous leishmaniasis (CL) is diverse in its clinical presentation but usually demonstrates an erythematous, infiltrated, ulcerated, and crusted papule or nodule in exposed areas of the body. Rare clinical features have been reported including lymphatic dissemination, usually with subcutaneous nodules along lymphatic channels. Herein, we present six patients suffering from Old World CL with lymphatic dissemination characterized by sporotrichoid subcutaneous nodules along the lymphatic channels drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Sporitrichoid CL dissemination is an uncommon presentation, but it has been reported as atypical presentation and many reports of evoked after intra-lesional treatment of the primary lesion. It has been described in three pattern of spread: 1) subcutaneous nodules in proximity to the primary lesion, 2) dilated palpable lymphatic vessels in form of a "beaded cord" and 3) reginal lumphadenitis.It is more seen in New World CL, In Old World, the exact prevalence is unknown but ranges from 10% -19% in the previous records, and the majority of the reported cases were shown to be caused by L. major and sometime due to L. tropica [24]. In Iraq, the sporotrichosis due to deep fungal infection or to other causes are not reported, but in CL, it is not a rare to see sporotrichoid lesions and present as a linear subcutaneous nodular lesions along the course of lymphatic although could superficial erythematous nodulations as seen in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Sporitrichoid CL dissemination is an uncommon presentation, but it has been reported as atypical presentation and many reports of evoked after intra-lesional treatment of the primary lesion. It has been described in three pattern of spread: 1) subcutaneous nodules in proximity to the primary lesion, 2) dilated palpable lymphatic vessels in form of a "beaded cord" and 3) reginal lumphadenitis.It is more seen in New World CL, In Old World, the exact prevalence is unknown but ranges from 10% -19% in the previous records, and the majority of the reported cases were shown to be caused by L. major and sometime due to L. tropica [24]. In Iraq, the sporotrichosis due to deep fungal infection or to other causes are not reported, but in CL, it is not a rare to see sporotrichoid lesions and present as a linear subcutaneous nodular lesions along the course of lymphatic although could superficial erythematous nodulations as seen in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…The characteristic wounds of the disease occur from the vector sting, which generates papules and later ulcerated lesions, being also possible the lymphatic spread of the parasite, causing new ulcerations. 21 The high incidence of notification of cases of imported ATL in the state of Paraíba can be explained by the fact that the treatment occurs in distinct localities of the zone of residence of the patient. This demonstrates that, despite the advances that have occurred in recent years, which pervade the historicity of social struggles for improvements in the health of the population, there is still complexity in the access to health services by the most socially vulnerable and needy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Sporotrichoid dissemination of cutaneous leishmaniasis can appear after local traumatism or puncture diagnostic [11] , however no local trauma was reported by our patient, nevertheless we recorded local application of corticosteroids, which probably can lead to the dissemination by a reduction in local immunity. Besides, it has been also suggested that tissue damage provoked by local therapy triggers the spread of leishmaniasis into the subcutis and lymphatic ducts [12] . Furthermore, the patient’s residence could contain strains of varying virulence that are irregularly distributed across transmission foci [3] .…”
Section: Discussionmentioning
confidence: 99%